(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aimed to determine the adequacy of the current financial statements of Iraqi agricultural companies to the needs of users of investors, government agencies and other concerned parties in making their economic decisions on the one hand and to show the reflection of the adoption and application of international financial reporting standards on the audit process at all stages when auditing animal and plant biological assets, and the researchers concluded that the different requirements of the audit process for financial statements prepared in accordance with local accounting rules and systems than when adopting and applying international accounting and financial reporting standards Which require procedures from the auditor to be different, especially when measuring animal or plant biological assets at fair value in light of the assessment and high personal judgment in most cases, and the research recommended the need to adopt the procedures for auditing biological assets presented by the researchers when auditing agricultural companies under the adoption and application of international financial reporting standards.